2014
DOI: 10.1186/1756-9966-33-49
|View full text |Cite
|
Sign up to set email alerts
|

A 41-gene signature derived from breast cancer stem cells as a predictor of survival

Abstract: PurposeThe aim of this study was to evaluate the ability of a 41-gene signature derived from breast cancer stem cells (BCSCs) to estimate the risk of metastasis and survival in breast cancer patients.MethodsThe centroid expression of the 41-gene signature derived from BCSCs was applied as the threshold to classify patients into two separate groups—patients with high expression (high-EL) of the prognostic signature and patients with low expression (low-EL). The predictive ability of the 41-gene signature was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Likewise, increased expression and activity of the enzyme ALDH1, which is one of the proposed CSC markers, significantly associated with poor outcomes in a cohort of 439 patients with serous ovarian cancer (Deng et al, 2010). Another study investigated the utility of a 41-gene signature derived from breast CSCs in a cohort of 198 patients and reported that patients with high CSC score had worse OS (Yin et al, 2014). This CSC signature was comparable to the commonly used Oncotype test and superior to MammaPrint for risk stratifying breast cancer patients.…”
Section: Prognostic Impact Of Cscs In Solid Tumorsmentioning
confidence: 99%
“…Likewise, increased expression and activity of the enzyme ALDH1, which is one of the proposed CSC markers, significantly associated with poor outcomes in a cohort of 439 patients with serous ovarian cancer (Deng et al, 2010). Another study investigated the utility of a 41-gene signature derived from breast CSCs in a cohort of 198 patients and reported that patients with high CSC score had worse OS (Yin et al, 2014). This CSC signature was comparable to the commonly used Oncotype test and superior to MammaPrint for risk stratifying breast cancer patients.…”
Section: Prognostic Impact Of Cscs In Solid Tumorsmentioning
confidence: 99%
“…One of the examples is a 21-gene classifer (Oncotype DX) ,which classifies breast tumors into low-,intermediate- and high-risk groups as to the advisability of adjuvant chemotherapy for patients in high-risk group [ 12 , 13 ]. The utility of such gene signature might have clinical potential to predict patient outcome and aid in treatment choice [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is a heterogeneous disease that comprises a range of subgroups with diverse clinical behaviors and responses to treatment [1]. Many breast-cancer-related genes have been investigated to explore the molecular mechanism of carcinogenesis and diverse clinical outcome of the disease [2][3][4][5][6]. Among them, some specific genes such as estrogen receptor (ER) [7], progesterone receptor (PR) [8] and human epidermal growth factor receptor 2 (HER2) [9] have been used to identify different subgroups and indicate different prognostic results with different treatment modalities in the clinical.…”
Section: Introductionmentioning
confidence: 99%